Inklusionsmaschine STADT - Benze, Andrea; Dorner, Maximilian; Hebert, Saskia; Häfner, Michael; Kegler, Karl R.; Leonhartsberger, Roman; Pfahl, Lisa; Polinna, Cordelia; Reiß-Schmidt, Stephan; Rummel, Dorothee; Saake, Irmhild; Trescher, Hendrik; et al. (JOVIS Verlag GmbH, 2021)
Inclusion in architecture and urban development is about much more than kitting out buildings and public spaces with technical components. It is essential to understand inclusion as a social concept, and to implement it as such-through hubs within the urban space, through locations that can withstand misconduct, and through open spaces, ordinances, and social mores. Inklusionsmaschine STADT addresses the subject of inclusion broadly, candidly, and thoroughly. The texts by authors from different disciplines demonstrate the wide range of interests involved and make it clear that inclusion can be an enriching process if stakeholders discuss the right questions together: is a city an inclusion machine? What components is it made up of? And who builds it?